2016
DOI: 10.1038/eye.2016.195
|View full text |Cite
|
Sign up to set email alerts
|

Real world outcomes of ocriplasmin use by members of the British and Eire Association of Vitreoretinal Surgeons

Abstract: Purpose To describe a survey of the use of ocriplasmin by members of the British and Eire Association of VitreoRetinal Surgeons (BEAVRS) for VitreoMacular Traction (VMT) and Full Thickness Macular Hole (FTMH) and compare it to published MIVI TRUST trial data. Methods All 173 BEAVRS members were contacted by email in October 2014 requesting data on all cases treated with ocriplasmin up to that date. The total number of cases, FTMH closure rate, VMT release rate and the frequency of adverse events were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…These results suggest that the known baseline factors predictive of VMA resolution, which were used as key inclusion criteria for the OASIS study, may be necessary but not sufficient to predict FTMH closure. Nevertheless, consistent with our findings, previous studies investigating FTMH closure rates following ocriplasmin treatment have repeatedly shown FTMH size at baseline to be the most consistent predictive factor, with a greater proportion of patients experiencing hole closure with an FTMH ≤ 250 m compared to those with an FTMH > 250-400 m. [14,36,37,44] In contrast, the natural history of untreated FTMH has revealed that spontaneous closure rates are low, ranging from 3-11%. [45][46][47][48][49] Although smaller holes have a comparatively better chance of spontaneous closure compared to larger ones, previous studies have shown that the majority of stage 2 macular holes (<400 m) progress to stage 3 and beyond if left untreated.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest that the known baseline factors predictive of VMA resolution, which were used as key inclusion criteria for the OASIS study, may be necessary but not sufficient to predict FTMH closure. Nevertheless, consistent with our findings, previous studies investigating FTMH closure rates following ocriplasmin treatment have repeatedly shown FTMH size at baseline to be the most consistent predictive factor, with a greater proportion of patients experiencing hole closure with an FTMH ≤ 250 m compared to those with an FTMH > 250-400 m. [14,36,37,44] In contrast, the natural history of untreated FTMH has revealed that spontaneous closure rates are low, ranging from 3-11%. [45][46][47][48][49] Although smaller holes have a comparatively better chance of spontaneous closure compared to larger ones, previous studies have shown that the majority of stage 2 macular holes (<400 m) progress to stage 3 and beyond if left untreated.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of adverse events was also greater than previously reported. 168,170 The benefits and risks associated with vitrectomy surgery versus intravitreal ocriplasmin require continued investigation.…”
Section: Microplasmin Intravitreal Injection For Non-surgical Treatmementioning
confidence: 99%
“…Sub-retinal fluid (SRF) following ocriplasmin intravitreal injection has been reported previously, particularly in eyes where traction has been successfully resolved. 6 , 8 , 10 , 13 , 14 , 15 , 16 , 17 Development of a serous detachment may be more common after ocriplasmin injection when compared to vitrectomy surgery. 18 Vitreomacular traction is rapidly resolved in vitrectomy surgery by peeling of the ILM with gas tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…Electroretinogram (ERG) changes post-ocriplasmin injection have also been reported. 5 , 6 , 7 , 8 , 9 , 10 These findings raise questions regarding the potential diffuse retinal effects of ocriplasmin injection. Transient and long-term effects of ocriplasmin injection require further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation